Kinerja Pegawai Pasca Restrukturisasi pada Direktorat SMA Kementerian Pendidikan Kebudayaan Riset dan Teknologi - Aulia Syafa Kurnia; Mawar Mawar; Abdul Rahman (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study aims to analyze the performance of employees of the Directorate of High Schools of the Ministry of Education, Culture, Research and Technology after the organizational restructuring. In this study, there is a problem, namely after the restructuring, the performance of employees of the Directorate of High School has not been fully optimal in working. This research uses employee performance theory according to Robbins, namely Quality, Quantity, Punctuality, Effectiveness, Independence and Work Commitment. The method used in this study is descriptive with a qualitative approach. This research was sourced from data from scientific journals, official websites, and supporting documents that describe the performance of employees at the Directorate of High Schools after the restructuring. The results showed that employee performance after restructuring was not optimal because employees were still being adjusted to the changes that occurred and there were still obstacles felt by employees in completing their work. However, the quality of performance provided for educational units (SMA) such as technical guidance and assistance services is good. The responsibility that employees have in completing their duties is good. However, there is still a low level of employee discipline in working hours.